Nutritional Implications of Baby-Led Weaning and Baby Food Pouches as Novel Methods of Infant Feeding: Protocol for an Observational Study - Taylor RW; Conlon CA; Beck KL; von Hurst PR; Te Morenga LA; Daniels L; Haszard JJ; Meldrum AM; McLean NH; Cox AM; Tukuafu L; Casale M; et al. (JMIR Publications, 2021)
BACKGROUND: The complementary feeding period is a time of unparalleled dietary change for every human, during which the diet changes from one that is 100% milk to one that resembles the usual diet of the wider family in less than a year. Despite this major dietary shift, we know relatively little about food and nutrient intake in infants worldwide and virtually nothing about the impact of baby food "pouches" and "baby-led weaning" (BLW), which are infant feeding approaches that are becoming increasingly popular. Pouches are squeezable containers with a plastic spout that have great appeal for parents, as evidenced by their extraordinary market share worldwide. BLW is an alternative approach to introducing solids that promotes infant self-feeding of whole foods rather than being fed purées, and is popular and widely advocated on social media. The nutritional and health impacts of these novel methods of infant feeding have not yet been determined. OBJECTIVE: The aim of the First Foods New Zealand study is to determine the iron status, growth, food and nutrient intakes, breast milk intake, eating and feeding behaviors, dental health, oral motor skills, and choking risk of New Zealand infants in general and those who are using pouches or BLW compared with those who are not. METHODS: Dietary intake (two 24-hour recalls supplemented with food photographs), iron status (hemoglobin, plasma ferritin, and soluble transferrin receptor), weight status (BMI), food pouch use and extent of BLW (questionnaire), breast milk intake (deuterium oxide "dose-to-mother" technique), eating and feeding behaviors (questionnaires and video recording of an evening meal), dental health (photographs of upper and lower teeth for counting of caries and developmental defects of enamel), oral motor skills (questionnaires), and choking risk (questionnaire) will be assessed in 625 infants aged 7.0 to 9.9 months. Propensity score matching will be used to address bias caused by differences in demographics between groups so that the results more closely represent a potential causal effect. RESULTS: This observational study has full ethical approval from the Health and Disability Ethics Committees New Zealand (19/STH/151) and was funded in May 2019 by the Health Research Council (HRC) of New Zealand (grant 19/172). Data collection commenced in July 2020, and the first results are expected to be submitted for publication in 2022. CONCLUSIONS: This large study will provide much needed data on the implications for nutritional intake and health with the use of baby food pouches and BLW in infancy. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTRN12620000459921; http://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=379436. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): DERR1-10.2196/29048.
Keywords: baby-led weaning; breast milk; choking; complementary feeding; dental health; diet; eating behavior; feeding behavior; food pouch; growth; infant; iron; 1103 Clinical Sciences; 1117 Public Health and Health Services